Efforts of Council Teacher in Reduce Peer Friends' Bad Prejudice at Madrasah Aliyah Laboratory StudentsiIn State Islamic University of North Sumatera - Khairuddin Tambusai (The Islamic Education and Multiculturalism Foundation, 2023)
Abstract: The research aims to find out: (1) The condition of peer prejudice towards Madrasah Aliyah Laboratory (MAL)students at State Islamic University (UIN) North Sumatra and (2) The efforts of counseling teachers in reducing prejudice against MAL students at UIN North Sumatra. The method used in this study is a qualitative method, research data collection is carried out by utilizing observation, interviews, and document review. The steps taken in analyzing the data are by compiling data, connecting data, reducing, presenting data then concluding. Through this research it was found that: (1) The occurrence of prejudice among peer students at MAL UIN-SU Medan was due to errors in reading incorrectly, responding incorrectly, hearing incorrectly, misunderstood, misunderstood, and misunderstood. The conclusions that arise from these mistakes will lead to unfavorable prejudices about something or someone. Among students also there is such a thing. Errors in various matters, as stated above, will create prejudice against his friends, even though this does not actually happen. (2) The efforts of the counseling teacher in reducing the occurrence of prejudice among MAL students at UIN North Sumatra. As for the forms of prejudice that occur among MAL students at UIN North Sumatra Medan, in the observations of researchers, there are several kinds. There are in the form of judging wrongly, staying away or not wanting to approach, bullying, physical harm and slander. All of these forms of prejudice will have a negative impact on students, and (3) The efforts made by the counseling teacher MAL UIN North Sumatra Medan teacher in reducing the occurrence of prejudice among their friends are by carrying out various activities aimed at reducing bad prejudice. At least two approaches have been taken. First by giving an example to each student that prejudice should not occur and showing the various negative consequences it causes. Second, by providing services that has been required in the counseling teacher.